2015
DOI: 10.1167/iovs.15-18036
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-483-3p Inhibits Extracellular Matrix Production by Targeting Smad4 in Human Trabecular Meshwork Cells

Abstract: PURPOSE. This study investigated the effects of microRNA-483-3p (miR-483-3p) on extracellular matrix (ECM) production, and clarified the regulatory mechanism of microRNA-483-3p in human trabecular meshwork cells (HTMCs) under oxidative stress. METHODS.The expression levels of ECM (fibronectin, laminin, collagen I) in HTMCs under oxidative stress were measured by Western blot. Changes of miR-483-3p expression in HTMCs were evaluated by quantitative polymerase chain reaction (qPCR). After using lentivirus stably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 42 publications
2
27
0
Order By: Relevance
“…As shown by western blots (Figure 2A), the relative protein levels of these ECM genes in the H 2 O 2 -treated cells were 1.81 ∼ 3.03 fold higher than the normal controls (Figure 2B, H 2 O 2 vs normal, p < 0.01 for Fibronectin, Laminin, and α-SMA; p < 0.05 for Collagen I). These results were consistent with previous studies [23, 24]. The results of immunofluorescence revealed that the fluorescence intensities of the ECM proteins in the cytoplasm under oxidative stress were substantially greater than those under normal condition (Figure 2C-2J).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…As shown by western blots (Figure 2A), the relative protein levels of these ECM genes in the H 2 O 2 -treated cells were 1.81 ∼ 3.03 fold higher than the normal controls (Figure 2B, H 2 O 2 vs normal, p < 0.01 for Fibronectin, Laminin, and α-SMA; p < 0.05 for Collagen I). These results were consistent with previous studies [23, 24]. The results of immunofluorescence revealed that the fluorescence intensities of the ECM proteins in the cytoplasm under oxidative stress were substantially greater than those under normal condition (Figure 2C-2J).…”
Section: Resultssupporting
confidence: 93%
“…The up-regulation of the ECM proteins in the HTMCs upon an acute exposure to oxidative stress (Figure 2A and 2B) was consistent with the studies conducted by us [23] and others [24, 31]. The increased production and cytoplasmic accumulation of the ECM proteins (Figure 2C-2J) will likely result in an increased deposition of key ECM components, such as fibronectin, collagen I, and laminin, in TM.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, the miRNA-29 family might regulate the effect of TGF-β on the extracellular matrix [32] . Our research team showed that miRNA-483-3p had an inhibitory effect on extracellular matrix production in the human trabecular meshwork cells through downregulating Smad4 [33] , which targeted TGF-β/bone morphogenetic protein [34] and laminin [35,36] . As a consequence, we may draw the conclusion that miRNA serves as a potential therapeutic target in influencing the development of glaucoma by regulating TGF-β, which affects the extracellular matrix.…”
Section: The Relationship Between Mirna and The Extracellular Matrix mentioning
confidence: 99%